Pelatihan penerapan model pembelajaran inovatif bagi guru Madrasah Aliyah Negeri 2 Kabupaten Magelang - Nurhidayah; Ary Kristiani; Diah Rahma Cahya Agustyowati; Aptia Ardiasri; Amanah (Universitas Negeri Yogyakarta, 2025)
Community Service Activities at MAN 2 Magelang aim to improve pedagogical competence in the application of innovative learning models that are tailored to the characteristics of students. Problems are solved through blended training methods, both offline and online. The activities included lectures, discussions, and practical application of learning models in the form of Lesson Plans (PP). The activities were conducted offline on June 13-14, 2025, and online via Zoom on August 29, 2025, attended by 62 teachers from MAN 2 Magelang with various subject backgrounds. The success of this activity can be measured in terms of process and product. In terms of process, the activity was successfully carried out according to the agreed schedule and was attended by participants in an orderly manner, as indicated by the participation of participants in each activity. In terms of product, this activity has produced teaching modules that have been compiled by teachers who have strived to implement innovative learning with diverse abilities. In addition, the mandatory output of the activity has also been compiled, namely the MoA manuscript, IA, media publications in Suara Merdeka Kedu on June 18, 2025, along with a draft article. There were no obstacles that arose in this activity because both the service team and partners were solid teams and there were no communication barriers. At the end of the activity, the partners hoped that there would be a continuation of similar training to further strengthen their abilities.